Peer Tutoring and Clinical Stage: analysis of experience and potential applications in the First Level Degree Course in Nursing, section of Desenzano Del Garda - Lo Biondo, Paolo; Avino, Nicola; Podavini, Enrica; Prandelli, Matteo (Acta Biomedica Atenei Parmensis, 2016)
There is a steady rise in the number of overseas students taking degree courses at the Medicine and Surgery faculties of Italian Universities. Numerous scholars, mainly from the English speaking world, have testified to the fact that a university teaching organisation aimed at attaining good levels of integration among students of differing cultural appurtenance is a prerequisite for success in the acquisition of good treatment practices. Aim: To explore the experience of students from Cameroon studying on the degree courses in Medicine and Surgery and in Nursing at the University of Parma, in order to discover the strong and weak points of the organisation of the courses so as to achieve a good process of integration. Materials and methods: An ethnographic study plan was adopted. In-depth interviews were conducted with 20 students from Cameroon enrolled in the Faculty of Medicine of Parma University: 10 in the Degree Course in Medicine and Surgery and 10 in the Degree Course in Nursing. The interviews were recorded and analysed independently by two researchers, who then pooled their results. The age of the interviewed ranges from 24 to 31, the average age is 26,5. Results: Independently from the attended degree course, most of the students interviewed claim that the process of integration has not been very successful: despite attempts to open up a dialogue with their Italian counterparts in order to get to know them, the latter showed no signs of willingness to integrate. Some students develop a self-critical attitude, maintaining that it would be a good idea to strengthen their awareness of their own cultural identity so as to start from a firm base in the attempt to open up to the host society without defensive attitudes that lead to ostracism. The difficulties of socialisation are compounded by those of learning, which many attribute to the language difficulties and some to the differing academic organisation between country of origin and host country. Discussion: The problem of the difficulties of integration of overseas students is not new. In other geographical locations, changes to syllabuses designed to solve the problem, at least in part, have been proposed and successfully implemented. The Italian situation is a particular one, and this preliminary study yields some ideas for the implementation of changes to the syllabuses of the Italian universities.